A theoretical strut model for severe seismic analysis of single-layer reticulated domes. (January 2017) - Ding, Yang; Chen, Zhao-Tao; Zong, Liang; Yan, Jia-Bao
Abstract: This paper focuses on proposing an efficient theoretical strut model to predict the post-buckling behaviors of members of single-layer reticulated domes under severe earthquake. The model was established based on finite element (FE) method and it can well reflect the performance of individual member during the complete loading period by using one element, especially the inelastic post-buckling behaviors. By using the model, the failure behavior of single-layer reticulated domes under severe earthquake can be well captured. With the help of this model, the interaction between individual member buckling and structural global instability can be accounted, and then the influence on plastic internal forces redistribution due to the degradation of bearing capacity of members under large displacement can be well depicted. The model is suitable for severe seismic analysis as it involves a wider range of strain than the existing phenomenological models. At last, the efficient model is verified by several experiments and good agreement is found between the simulated and experimental results. Highlights: An efficient theoretical model is proposed to predict the post-buckling behaviors of members. The interaction between individual member buckling and structural global instability can be accounted by this model. Modeling and computational efficiency have been improved due to fewer elements used in the theoretical model. The model is verified by several experiments on individual members and global structures